Integration of Lateral Thinking in Puzzle Games: Implications for Creativity and Problem Solving - Fikri Hendaputra, Raden Mohammad; Ratri, Dianing (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
Creative thinking and problem-solving are essential skills that adolescents need to navigate the challenges of the 21st century. Unfortunately, formal education systems still tend to emphasize linear thinking and often fall short in providing space to nurture cognitive flexibility. One alternative approach that has shown promise is lateral thinking—a non-linear thinking method that can be effectively applied through puzzle games. This study aims to explore late adolescents’ perceptions of the effectiveness of lateral thinking in puzzle games, as well as the potential of such games in fostering creativity and problem-solving skills. A descriptive qualitative approach was employed using Focus Group Discussion (FGD) as the primary method. Ten participants aged 17–22 took part in a structured discussion about their gaming experiences and their perspectives on the concept of lateral thinking. The data were analyzed thematically. The findings indicate that most participants viewed lateral thinking as an effective approach for tackling problems that require creative solutions. Puzzle games designed with contextual challenges, tiered reward systems, and engaging narratives were considered effective in stimulating idea exploration and flexible thinking. Social features such as multiplayer modes and strategy discussions were also seen as enhancing motivation and cognitive collaboration among players. Participants reported that they began applying alternative thinking patterns in real-life situations, such as when developing organizational strategies or resolving social conflicts. This suggests a transfer of skills from the gaming environment to real-world contexts. In conclusion, integrating lateral thinking into puzzle game design presents a relevant educational approach to enhance adolescents' thinking skills. These types of games hold great potential as enjoyable alternative learning tools that simultaneously build cognitive capacity.